Retrospective review of safety and efficacy of programmed cell death-1 inhibitors in refractory high grade gliomas. Issue 1 (19th December 2017) - Reiss, Samantha N.; Yerram, Prakirthi; Modelevsky, Lisa; Grommes, Christian
Abstract : Background: Programmed cell death ligand-1 (PD-L1) expression has been reported in up to 61% of high grade gliomas (HGG). The purpose of this study was to describe safety and efficacy of PD-1 inhibition in patients with refractory HGGs. Methods: This Institutional Review Board approved single center retrospective study included adult patients with pathologically confirmed HGG who received a PD-1 inhibitor from 9/2014–10/2016 outside of a clinical trial at Memorial Sloan Kettering Cancer Center. Results: Twenty five HGG patients received pembrolizumab as part of a compassionate use program. Median age was 50 years (range 30–72); 44% were men; 13 had glioblastoma (52%), 7 anaplastic astrocytoma (28%), 2 anaplastic oligodendroglioma (8%), 2 unspecified HGG (8%), and 1 gliosarcoma (4%). Median prior lines of treatments were 4 (range 1–9). Nineteen (76%) previously failed bevacizumab. Median KPS was 80 (range 50–100). Concurrent treatment included bevacizumab in 17 (68%) or bevacizumab and temozolomide in 2 (8%) patients. Median number of doses administered was 3 (range 1–14). Outcomes were assessed in 24 patients. PD-1 inhibitor related adverse events included LFT elevations, hypothyroidism, diarrhea, myalgias/arthralgias, and rash. Best radiographic response was partial response ( n = 2), stable disease ( n = 5), and progressive disease ( n = 17). Median progression free survival (PFS) was 1.4 months (range 0.2–9.4) and median overall survival (OS) was 4 months (range 0.5–13.8). Three-month PFS was 12% and 6-month OS was 28%. Conclusion: While response rates are low, a few patients had a prolonged PFS. Pembrolizumab was tolerated with few serious toxicities, even in patients receiving concomitant therapy.